Gauge-equivariant flow models for sampling in lattice field theories with pseudofermions - Abbott, Ryan; Albergo, Michael S.; Boyda, Denis; Cranmer, Kyle; Hackett, Daniel C.; Kanwar, Gurtej; Racanière, Sébastien; Rezende, Danilo J.; Romero-López, Fernando; Shanahan, Phiala E.; Tian, Betsy; Urban, Julian M. (Physical review, 2022)
This work presents gauge-equivariant architectures for flow-based sampling in fermionic lattice field theories using pseudofermions as stochastic estimators for the fermionic determinant. This is the default approach in state-of-the-art lattice field theory calculations, making this development critical to the practical application of flow models to theories such as QCD. Methods by which flow-based sampling approaches can be improved via standard techniques such as even/odd preconditioning and the Hasenbusch factorization are also outlined. Numerical demonstrations in two-dimensional U(1) and SU(3) gauge theories with Nf=2 flavors of fermions are provided.
Gesehen am 27.01.2023